Pseudoxanthoma Elasticum: A Streamlined, Ethnicity‐based Mutation Detection Strategy - LaRusso, Jennifer (Blackwell Publishing Inc, 2010)
Pseudoxanthoma elasticum (PXE), an autosomal recessive multisystem disorder, is caused by mutations in the ABCC6 gene, and approximately 300 distinct mutations representing >1,000 mutant alleles have been disclosed thus far. Few population‐based studies have reported mutational hotspots in some geographic areas. In this study, we attempted to correlate recurring mutations with the individuals’ ethnic origin. Specifically, we plotted our international database of 70 families from distinct or mixed ethnic backgrounds against their mutations. The frequent p.R1141X mutation was distributed widely across Europe, while deletion of exons 23–29 (del23–29) was encountered in Northern Europe and in Northern Mediterranean countries. p.R1138W may be a marker for French descent, evidenced by its presence also in French Canadians. The splice site transition mutation 3736–1G→A was seen in the neighboring countries Greece and Turkey, whereas 2542 delG occurs only in the Japanese. Two mutations seem to be present worldwide without evidence of a founder effect, p.Q378X and p.R1339C, suggesting the presence of mutational hotspots. Knowledge of this distribution will allow us to streamline mutation screening through a targeted, stepwise approach when the ethnicity of a patient is known. This will facilitate the identification of individuals at risk, improving their care to prevent ophthalmological and vascular disease. Clin Trans Sci 2010; Volume 3: 295–298